Maternal benzo[a]pyrene exposure during critical gestational periods impairs offspring neurological development in rats: a mechanistic study of the Wnt/β-catenin signaling pathway - Zhang, Nan; Bo, Nan; Wang, Yuanhao; Bai, Wenlin; Sun, Wen; Zhao, Zhenlin; Zhang, Yuanbao; Zhang, Yingying; Lei, Lijian; Zhou, Jianjun; Zhang, Wenping (Frontiers in Behavioral Neuroscience, 2025)
IntroductionMid-gestation is a critical period for the development of the nervous system. Exposure to exogenous harmful chemicals during this period may lead to longterm neurological developmental abnormalities in offspring. Benzo[a]pyrene (B[a]P) is a commonly occurring neurotoxic environmental pollutant that can pass through the placental barrier and blood-brain barrier (BBB), thereby affecting placental nerve development.MethodsTo investigate the neurotoxic mechanism of B[a]P on offspring exposed in mid-gestation, pregnant rats were exposed to B[a]P (25 mg/kg) from gestation days 8 to 14. Meanwhile, as an agonist of Wnt/β-catenin signaling pathway, lithium chloride (LiCl) was administered to observe the intervention effects.ResultsThe results showed that in rats exposed to B[a]P in mid-gestation, the developmental nodes of the offspring were delayed, and the neurosensory sensitivity of the offspring was reduced. These offspring also had cognitive impairments in adulthood. Subsequent morphological and protein experiments showed that the exposed offspring had reduced neuronal complexity in the CA1 region of the hippocampus, decreased β-catenin expression, and increased GSK-3β expression in the hippocampal tissue. However, all these indexes can be reversed by LiCl.DiscussionThese results suggest that B[a]P exposed in mid-gestation pregnancy may lead to neurological damage in the offspring by downregulating the Wnt/β-catenin signaling pathway.